Skin recruitment of monomyeloid precursors involves human herpesvirus‐6 reactivation in drug allergy. Issue 5 (10th April 2013) - Hashizume, H.; Fujiyama, T.; Kanebayashi, J.; Kito, Y.; Hata, M.; Yagi, H.
Abstract Background In drug‐induced hypersensitivity syndrome (DIHS), latent human herpesvirus (HHV)‐6 is frequently reactivated in association with flaring of symptoms such as fever and hepatitis. We recently demonstrated an emergence of monomyeloid precursors expressing HHV‐6 antigen in the circulation during this clinical course. Methods To clarify the mechanism of HHV‐6 reactivation, we immunologically investigated peripheral blood mononuclear cells (PBMCs), skin‐infiltrating cells, and lymphocytes expanded from skin lesions of patients with DIHS. Results The circulating monomyeloid precursors in the patients with DIHS were mostly CD11b+CD13+CD14−CD16high and showed substantial expression of skin‐associated molecules, such as CCR4. CD13+CD14− cells were also found in the DIHS skin lesions, suggesting skin recruitment of this cell population. We detected high levels of high‐mobility group box (HMGB)‐1 in blood and skin lesions in the active phase of patients with DIHS and showed that recombinant HMGB‐1 had functional chemoattractant activity for monocytes/monomyeloid precursors in vitro. HHV‐6 infection of the skin‐resident CD4+ T cells was confirmed by the presence of its genome and antigen. This infection was likely to be mediated by monomyeloid precursors recruited to the skin, because normal CD4+ T cells gained HHV‐6 antigen after in vitro coculture with highly virus‐loaded monomyeloid precursors from the patients. Conclusions Our results suggest that monomyeloid precursors harboring HHV‐6 are navigated by HMGB‐1 released from damaged skin and probably cause HHV‐6 transmission to skin‐infiltrating CD4+ T cells, which is an indispensable event for HHV‐6 replication. These findings implicate the skin as a cryptic and primary site for initiating HHV‐6 reactivation.